Suffering in Silence: Violence Exposure and Post-Traumatic Stress Disorder Among Jail Correctional Officers. Issue 1 (5th November 2021) - Ellison, Jared M.; Jaegers, Lisa A.
Abstract : Objective: Correctional officers are exposed to violence more often than many other public service workers, yet little is known about the traumatic nature of these risks. We examine violence exposure and post-traumatic stress disorder (PTSD) among a large, multi-facility sample of jail officers. Method: One thousand three hundred and sixty five officers working in 20 jails were surveyed regarding background characteristics, exposure to violence at work, and post-traumatic stress symptoms measured by the PTSD Checklist for DSM-5 (PCL-5). Results: About one-third of the sample met the criteria for a "provisional PTSD Diagnosis" or "probable PTSD".' Victimization and exposure to violence, both in and outside of work, significantly contributed to PTSD symptoms. Conclusions: Findings highlight the severity of, and link between, exposure to violence and PTSD among jail officers. Implications for diagnosing, treating, and preventing PTSD among jail officers are discussed.